THE IMPORTANCE OF PECTIN IN MEDICINE FROM NATURAL POLYSACCHARIDES (World Bulletin of Public Health, 2024)
In this scientific article, we will talk about the medical significance of pectin from natural polysaccharides and its biochemical basis. Pectin is a natural polysaccharide, which is mainly found in the cell walls of plants. It consists of galacturonic acid residues and is soluble in water. The wide application of pectin in medicine is associated with its biologically active properties. Pectin binds with water and forms a gel. This property allows it to be used in medical preparations and food additives. Pectin binds heavy metals, radioactive isotopes and toxins and removes them from the body. This feature is important for people exposed to environmental pollution or poisoning. Pectin improves intestinal microflora and ensures the growth of beneficial bacteria. Pectin protects cells from free radicals. reduces oxidative stress in the body.
Keywords: Pectin; polysaccharide; biochemical properties; medicine